Literasi Keuangan Pada Masyarakat Desa Bola Bulu Kecamatan Pitu Riase Kabupaten Sidenreng Rappang Sulawesi Selatan (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Financial literacy is still the homework of all parties, including financial institutions and authorities. Seeing the scope of financial literacy, namely regarding the understanding of features, benefits, risks, and obligations related to financial products and services, efforts to increase public understanding still need to be socialized. Moreover, financial literacy also measures the correct level of skills, attitudes, and behavior in using financial products and services. Looking at various cases, financial institutions and authorities are still inferior to the ways in which financial criminals offer their services to the public. Efforts to improve financial literacy are also the responsibility of academics from universities. On that basis, this community service activity which is part of the Independent Learning Campus program (MBKM) was carried out for the people of Bola Bulu Village. The method used is empowerment and capacity building through several stages, namely engagement, assessment, planning, intervention, and evaluation. The results of the program show that this activity was enthusiastically participated in by the community and was considered very beneficial for them because it has given them a clear understanding to be wise and careful in conducting financial transactions online, be it in the form of arisan or fraudulent investments, online shopping, and loans.